Sociology in modules - Schaefer, Richard T. (McGraw Hill LLC, 2023)
"Sociology in Modules, sixth edition, bridges the essential sociological theories, research, and concepts and the everyday realities we all experience. The program highlights the distinctive ways in which sociologists explore human social behavior and how their research findings can be used to help students think critically about the broader principles that guide their lives"--Provided by publisher.